Modelling Long-Term Outcomes and Risk of Death for Patients with Post-Stroke Spasticity Receiving Abobotulinumtoxina Treatment and Rehabilitation Therapy - Klemens Fheodoroff; Natalya Danchenko; John Whalen; Jovita Balcaitiene; Barbara Magalhães; Elzbieta Szulc; Andrea Zaffalon; Mariya Burchakova; Dmitry Nechiporenko; Sean Robbins (Medical Journals Sweden, 2022)
Objective: Stroke is associated with a high risk of death and cardiovascular events. Rehabilitation therapy is critical for functional recovery, to reduce hospital readmissions, all-cause and cardiovascular mortality, and stroke recurrence (long-term outcomes). Post-stroke spasticity may prevent effective recovery by restricting mobility. AbobotulinumtoxinA is an adjunctive therapy to physical therapy for post-stroke spasticity, but its long-term effects are unknown. The objective was to model the long-term clinical and economic outcomes of abobotulinumtoxinA for post-stroke spasticity. Methods: Effects of abobotulinumtoxinA on treating post-stroke spasticity and evidence linking functional outcomes with long-term outcomes were collected in a focused literature review. A model was developed to estimate health benefits on long-term outcomes, direct medical costs, life- and qualityadjusted life-years for abobotulinumtoxinA injections plus rehabilitation therapy compared with rehabilitation therapy alone, from a UK perspective over a 10-year time-period. Results: AbobotulinumtoxinA + rehabilitation therapy led to a risk reduction of 8.8% for all-cause mortality, and an increase of 13% in life-years and 59% in quality-adjusted life-years compared with rehabilitation therapy alone. AbobotulinumtoxinA + rehabilitation therapy was considered cost-effective compared with rehabilitation therapy alone (incremental cost-effectiveness ratio: £24,602). Conclusion: AbobotulinumtoxinA + rehabilitation therapy may improve long-term outcomes, including post-stroke survival, while being cost-effective for the treatment of post-stroke spasticity. LAY ABSTRACT Here we developed a model to explore and compare the long-term benefits and overall costs of two interventions for the treatment of post-stroke spasticity (PSS): abobotulinumtoxinA injections plus rehabilitation therapy (aboBoNT-A+RT) vs. RT alone. Stroke survivors are known to be at a higher risk of recurrent stroke and death, and more than 25% are affected by spasticity. PSS significantly reduces patients' mobility, physical functioning, and subsequently their ability to recover after a stroke. AboBoNT-A+RT is an effective treatment for spasticity. This model is the first to highlight that combining aboBoNT-A injections with RT could improve the overall survival of stroke survivors with spasticity by 8.8% and their overall quality of life, while being considered good value for money by UK payers.